2014
DOI: 10.1055/s-0034-1389904
|View full text |Cite
|
Sign up to set email alerts
|

Systemic LPS and Inflammatory Response during Consecutive Days of Exercise in Heat

Abstract: This investigation studied circulating LPS activity, potential intestinal damage, and the systemic inflammatory response (SIR) during the exercise heat acclimation process. 8 healthy males (Age=24±3 years) ran in a hot environment on 5 consecutive days until core temperature (Tc) was elevated 2°C above rest. Plasma was obtained pre-, post-, 1 h post-, and 3 h post-exercise on the 1(st), 3(rd), and 5(th) day of exercise and analyzed for TNF-α, IL-6, IL-10, IL-1ra, LPS, and intestinal fatty acid-binding protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
30
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 44 publications
(79 reference statements)
6
30
1
1
Order By: Relevance
“…Agreeing with previous literature, larger ΔIL-6 and ΔTNF-a were observed during HA compared to TEMP (Fig. 3) (Starkie et al 2005;Peake et al 2007;Hailes et al 2011;Kuennen et al 2011;Barberio et al 2015;Guy et al 2016;Lee et al 2018). The larger responses observed for Δcortisol for sessions 5 and 10, but not 1 (Armstrong et al 1990;Hargreaves et al 1996;Brenner et al 1997;Starkie et al 2005;Peake et al 2007;Cooper et al 2010;Hosick et al 2010) during HA are a response to increased physiological strain due to the heat stress for the same absolute exercise intensity (e.g., higher T re , ΔT re and HR) (Starkie et al 2005).…”
Section: Inflammatory and Stress Responsessupporting
confidence: 84%
See 1 more Smart Citation
“…Agreeing with previous literature, larger ΔIL-6 and ΔTNF-a were observed during HA compared to TEMP (Fig. 3) (Starkie et al 2005;Peake et al 2007;Hailes et al 2011;Kuennen et al 2011;Barberio et al 2015;Guy et al 2016;Lee et al 2018). The larger responses observed for Δcortisol for sessions 5 and 10, but not 1 (Armstrong et al 1990;Hargreaves et al 1996;Brenner et al 1997;Starkie et al 2005;Peake et al 2007;Cooper et al 2010;Hosick et al 2010) during HA are a response to increased physiological strain due to the heat stress for the same absolute exercise intensity (e.g., higher T re , ΔT re and HR) (Starkie et al 2005).…”
Section: Inflammatory and Stress Responsessupporting
confidence: 84%
“…The larger responses observed for Δcortisol for sessions 5 and 10, but not 1 (Armstrong et al 1990;Hargreaves et al 1996;Brenner et al 1997;Starkie et al 2005;Peake et al 2007;Cooper et al 2010;Hosick et al 2010) during HA are a response to increased physiological strain due to the heat stress for the same absolute exercise intensity (e.g., higher T re , ΔT re and HR) (Starkie et al 2005). Our changes in IL-6 (+55%), TNF-a (+45%) and cortisol (+34%) during HA were comparable in ODHA and TDHA, and are less than, or comparable to, responses published elsewhere (IL-6: +20-2000%, TNF-a: +15-65%, and cortisol: +20-70%) (Armstrong et al 1990;Brenner et al 1997;Starkie et al 2005;Peake et al 2007;Hosick et al 2010;Hailes et al 2011;Kuennen et al 2011;Barberio et al 2015;Guy et al 2016;Costello et al 2018). Our findings also agree with reported transient ΔIL-6 during MTHA (Guy et al 2016;Costello et al 2018) alongside induced heat adaptations (Rendell et al 2017) and no evidence of chronic inflammatory effects or signs of exaggerated ΔTNF-a (e.g., possible endotoxemia) (Guy et al 2016).…”
Section: Inflammatory and Stress Responsessupporting
confidence: 54%
“…Following both EHSTs, I‐FABP increased by approximately 50% or 0.800 ng ml −1 . This response is comparable to numerous similar duration/intensity exercise protocols, such as: 45‐to‐60 min of ~70% watt max normothermic cycling (van Wijck et al, , [61%, Δ 0.306 ng ml −1 ] 2012, [61%; Δ 0.179 ng ml −1 ] and 20–30 min of ~80% VO 2max running (Barberio et al, [46%, Δ 0.297 ng ml −1 ]; March et al, [72%; Δ 0.350 ng ml −1 ]). In comparison, far greater elevations in I‐FABP have been shown following 90–120 min of moderate‐intensity running performed in the heat (30°C; Morrison, Cheung, & Cotter, [663%; Δ 0.203–0.806 ng ml −1 ]; Snipe et al, [288%, Δ 0.897 ng ml −1 ]; 2018 [432%, Δ 1.230 ng ml −1 ].…”
Section: Discussionsupporting
confidence: 71%
“…Indeed Morrison et al (2014) have reported an increase in I-FABP of 563% following 90 min of cycling and running in 30°C with an end core temperature of 38.75°C, while Barberio et al (2015) reported an increase of only 46% following 26 min of running in 40 degrees with an end core temperature of 39.0°C at a similar intensity. In support of the hypothesis that the magnitude of exercise induced intestinal damage is not related to environmental temperature we have combined the present group mean data with data from other studies that simultaneously report the post-exercise change in I-FABP in combination with end exercise core temperature, participants V O 2max (indicative of training status), and exercise duration and intensity (Morrison et al 2014;Barberio et al 2015;March et al 2017;McKenna et al 2017;Snipe et al 2018a). There was a significant correlation between environmental temperature (range 22°C to 40°C) and end exercise core temperature (range 38.2°C to 39.6°C) (r=0.79, p=0.011), however; there was no significant correlation between the magnitude of intestinal damage and core temperature (r=0.3, p=0.43), suggesting that other factors contribute to the extent of damage.…”
Section: Discussionmentioning
confidence: 99%